Serum proteomic assessment of the progression of fracture healing. Issue 4 (22nd November 2017) - Hussein, Amira I.; Mancini, Christian; Lybrand, Kyle E.; Cooke, Margaret E.; Matheny, Heather E.; Hogue, Brenna L.; Tornetta, Paul; Gerstenfeld, Louis C.
ABSTRACT: A targeted proteomic analysis of murine serum over a 35‐day course of fracture healing was carried out to determine if serum proteomic changes could be used to monitor the biological progression of fracture healing. Transverse, closed femoral fractures where generated and stabilized with intramedullary fixation. A single stranded DNA aptamer‐based multiplexed proteomic approach was used to assay 1, 310 proteins. The transcriptomic profiles for genes matching the 1, 310 proteins were obtained by microarray analysis of callus mRNA. Of the 1, 310 proteins analyzed, 850 proteins showed significant differences among the time points ( p ‐value <0.05). Ontology assessment associated these proteins with osteoblasts, monocyte/macrophage lineages, mesenchymal stem cell lines, hepatic tissues, and lymphocytes. Temporal clustering of these data identified proteins associated with inflammation, cartilage formation and bone remodeling stages of healing. VEGF, Wnt, and TGF‐βsignaling pathways were restricted to the period of cartilage formation. Comparison of the proteomic and transcriptomic profiles showed that 87.5% of proteins in serum had concordant expression to their mRNA expression in the callus, while 12.5% of the protein and mRNA expression patterns were discordant. The discordant proteins that were elevated in the serum but down regulated in callus mRNA expression were related to clotting functions, allograft rejection, and complement function. While proteins down regulated in the serum and elevated in callus mRNA were associated with osteoblast function, NF‐ĸb, and activin signaling. These data show the serum proteome may be used to monitor the different biological stages of fracture healing and have translational potential in assessing human fracture healing. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1153–1163, 2018.